UPAYA MENINGKATKAN PEMAHAMAN TEKS SISWA KELAS IV SDN JERUK 1 SURABAYA MENGGUNAKAN MEDIA BIG BOOK - Putri Muldash, Nency; Dwi Wicaksono, Vicky; Rohmah, Hidayatur; Yulia Alfia Novita, Icha; Bagus Firmansyah, Imaduddin; Andaresta, Kevin; Kurniawati, Lilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Classroom Action Research (CAR) aims to improve the reading comprehension skills of fourth-grade students at SDN Jeruk 1 Surabaya through the implementation of Big Book media. The study was conducted in two cycles involving 23 students as research subjects. The research method employed the Kemmis and McTaggart CAR model, consisting of four stages: planning, implementation, observation, and reflection. Data were collected through observations of teacher and student activities, as well as reading comprehension tests, and analyzed using qualitative and quantitative approaches. The results demonstrated significant improvement in students' reading comprehension. In Cycle I, the classical mastery level reached 60.8% with an average score of 66.8, while in Cycle II, it increased to 82.6% with an average score of 77.6. This improvement was supported by enhanced learning activities, including more interactive use of Big Book media, increased student participation, and better summarization skills. Observations also revealed heightened student interest and motivation, with the majority showing enthusiasm and engagement in collaborative reading activities. The study concludes that Big Book media is effective in enhancing elementary students' reading comprehension. Its strengths lie in its visually appealing design and enjoyable learning approach, which create a meaningful classroom atmosphere. This research contributes significantly to the development of literacy teaching methods, particularly in addressing reading comprehension difficulties at the elementary level. The study recommends broader implementation of Big Book media in Indonesian language instruction.